Practical Clinical Andrology - Bettocchi, Carlo; Busetto, Gian Maria; Carrieri, Giuseppe; Cormio, Luigi (Springer International Publishing : Imprint: Springer, 2023)
This open access book offers a valuable resource for understanding the correct pathways in the context of sexual disorders, couple reproduction, gender identity dysphoria, conditions for which patients commonly ask for consultation and treatment. Based on clinical evidence, international guidelines and experts experience, practical clinical management strategies are presented for each condition. Each clinical care pathway is based on updated algorithm, level of evidence, photos and video-clips that describes the clinical presentations and the best practice management through diagnostic tools and medical or surgical treatment. Leading experts from the most important center of excellence in the field of sexual medicine joined to cover the field of andrology in its entirety, each of them dealing with a single topic from the top of their recognized experience and providing a complete and update textbook that will help urologists and other physicians in their daily clinical practice. This book is thought to be a practical and valuable reference for urologists, gynecologists, endocrinologists, psychiatrics and psychologists, and residents who are not specialty trained in andrology. It is designed for both young fellows training in different specialties and coming into contact with andrological issues for the first time and also more experienced clinicians and surgeons requiring updated guidelines and clear advice on the most controversial issues. This book will represent an invaluable quick consulting tool, updated in its scientific contents and rich in tables, images and video-clips.